The Cerebrospinal Fluid Profile of Cholesterol Metabolites in Parkinson’s Disease and Their Association With Disease State and Clinical Features - Griffiths, William J.; Abdel-Khalik, Jonas; Moore, Sarah F.; Wijeyekoon, Ruwani S.; Crick, Peter J.; Yutuc, Eylan; Farrell, Krista; Breen, David P.; Williams-Gray, Caroline H.; Theofilopoulos, Spyridon; Arenas, Ernest; Trupp, Miles; et al. (Frontiers in Aging Neuroscience, 2021)
Disordered cholesterol metabolism is linked to neurodegeneration. In this study we investigated the profile of cholesterol metabolites found in cerebrospinal fluid (CSF) of Parkinson’s disease (PD) patients. When adjustments were made for confounding variables of age and sex, 7alpha,(25R)26-dihydroxycholesterol and a second oxysterol 7alpha,x,y-trihydroxycholest-4-en-3-one (7alpha,x,y-triHCO), whose exact structure is unknown, were found to be significantly elevated in PD CSF. The likely location of the additional hydroxy groups on the second oxysterol are on the sterol side-chain. We found that CSF 7alpha-hydroxycholesterol levels correlated positively with depression in PD patients, while two presumptively identified cholestenoic acids correlated negatively with depression.